Clinical Characteristics and Glycemic Outcomes of Patients with Type 2 Diabetes Requiring Maximum Dose Insulin Glargine/Lixisenatide Fixed-Ratio Combination or Insulin Glargine in the LixiLan-L Trial - Blonde, Lawrence (Adv Ther, 2019)
INTRODUCTION: iGlarLixi is a titratable, fixed-ratio combination of insulin glargine (iGlar, 100 units/ml) and the glucagon-like peptide-1 receptor agonist lixisenatide for the treatment of patients with type 2 diabetes. This post hoc analysis of the phase 3 LixiLan-L trial (NCT02058160) investigated baseline characteristics, glycemic control, and safety outcomes in participants who received the study-specified maximum dose (60 units/day) of iGlarLixi or iGlar vs. those who received < 60 units/day. METHODS: Outcomes were compared for participants receiving 60 or < 60 units/day at week 30. Endpoints analyzed included change in A1C, fasting plasma glucose (FPG), 2-h postprandial glucose (2-h PPG), body weight, proportion of participants achieving A1C < 7.0%, proportion of participants receiving rescue therapy, documented symptomatic hypoglycemia, and gastrointestinal adverse event (GI AE) incidence. RESULTS: By week 30, 27% (iGlarLixi) and 31% (iGlar) of participants received the maximum dose. Participants on 60 vs. < 60 units/day were younger and had higher body weight, body mass index (BMI), FPG, and baseline insulin dose. In both dose groups, A1C change from baseline was significantly greater with iGlarLixi vs. iGlar, and more participants treated with iGlarLixi vs. iGlar achieved A1C < 7.0%. No significant differences were observed in change from baseline for A1C, FPG, 2-h PPG, or GI AE incidence between insulin dose groups, regardless of treatment. In both treatment arms, incidence of symptomatic hypoglycemia was lower in participants receiving 60 units/day vs. those receiving < 60 units/day. Participants treated with iGlarLixi (< 60 or 60 units/day) had modest weight loss over 30 weeks vs. an increase in weight compared with iGlar. CONCLUSIONS: Maximum doses of iGlarLixi were required in participants with a more insulin-resistant clinical phenotype (younger, higher BMI, FPG, and insulin doses). Benefits were observed with iGlarLixi vs. iGlar, even at 60 units/day, with more participants achieving glycemic goals, no increase in symptomatic hypoglycemia, and a modest reduction in body weight. FUNDING: Sanofi US, Inc. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12325-019-01033-1) contains supplementary material, which is available to authorized users.